Effective boundary conditions and turbulence modeling for the analysis of steam turbine exhaust hood. (25th June 2016) - Veerabathraswamy, K.; Senthil Kumar, A.
Highlights: Effective inlet and outlet boundary conditions obtained for a reduced model. Flow characteristics of backward facing step are correlated for the exhaust hood. Domain extension at the outlet is recommended for computational stability. Proposed computational model is validated against experimental results. Flow physics for pressure loss and flow non uniformity is investigated. Abstract: The steam turbine exhaust hood is a stationary component which connects the last stage of the turbine exit to the condenser. An optimal geometric design of the exhaust hood is typically achieved through multiple design iterations in conjunction with computational methods estimating the performance of every such design. To satisfy the need of quick performance estimation, a reduced computational model with the inlet of the computational domain at the trailing edge plane of the last stage rotor is commonly used. The main challenge in using a reduced computational model is selection of appropriate inlet and outlet boundary conditions, as the flow condition at these boundaries are not known. In this work, the boundary condition options for the outlet where a significant reverse flow is expected are studied, along with studying the effect of condenser tubes on the flow regime. Use of total pressure, mass flow rate and velocity boundary conditions at the inlet along with extended domain options are evaluated for inlet boundary modeling. In addition, a comprehensive study of turbulence models with respect to their ability to predict the pressure loss is reported. A recommendation on the turbulence model and boundary conditions for the exhaust hood modeling is arrived at, which is validated with experimental results. The implementation of recommended inlet, outlet boundary conditions and turbulence model produced consistent results with 9% reduced computational effort.